Analisis Pengelolaan Dana BOS Sebelum Dan Selama Pandemi Covid-19 Di SMA Negeri 2 Sungai Limau - Mustapa Mustapa; Novi Yanti; Fakhri Zaki; Syamsurizal Syamsurizal (Institut Agama Islam Sumatera Barat, 2021)
This research is entitled Analysis of BOS Fund Management Before and During the Covid-19 Pandemic at SMA Negeri 2 Sungai Limau, Padang Pariaman Regency. This is a descriptive qualitative research to find out how the description of the management of Regular BOS funds at SMA Negeri 2 Sungai Limau in 2019 (before the Covid19 pandemic) and 2020 (the Covid-19 pandemic) by referring to government policies through the Minister of Education and Culture which are the respective Technical Guidelines. that year. The method used in this research is descriptive research method with a qualitative approach. Researchers collect data through interviews with the school's BOS Team and documentation. The results of this study indicate that the implementation of BOS fund management before and during the Covid-19 pandemic at SMA Negeri 2 Sungai Limau, in 2019 and 2020 in general in terms of planning, implementation, monitoring and evaluation as well as reporting that was carried out was in accordance with the technical instructions of BOS SMA. . The publication aspect of the management of the BOS Fund has not utilized the means of announcement for easy accessibility of information for the public.